2018
DOI: 10.1590/1807-3107bor-2018.vol32.0101
|View full text |Cite
|
Sign up to set email alerts
|

Pacifier use modifies the association between breastfeeding and malocclusion: a cross-sectional study

Abstract: This study aimed to evaluate the influence of breastfeeding and pacifier use on the occlusal status of preschool children. A crosssectional study was conducted with children (n = 489) aged 2-5 years in private and public schools in Pelotas, South Brazil. Mothers answered a questionnaire on demographic, socioeconomic and behavioral variables, including breastfeeding and non-nutritive sucking habits. Malocclusion was classified as normal/mild and moderate/severe, according to WHO criteria. The association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 21 publications
0
24
0
2
Order By: Relevance
“…1 This instruction takes into account the possibility of "nipplesconfusion" by the infant, resulting in an oral configuration and sucking pattern inappropriate for breastfeeding after exposure to the artificial nipples, 2 which contributes to early weaning. 3 Studies have shown that the use of pacifiers and/or feeding bottle favors early breastfeeding discontinuance, interferes with the development of orofacial structures, alterschild chewing and swallowing functions, 4 is associated with higher risk of cariesoccurrence 5 and teeth malocclusion, 6 besides it has been considered an important source of contamination by microorganisms harmful to health. 7 In Brazil, some regulations were established in order to supervise the trade of infant products, including pacifiers and baby bottles.…”
Section: Introductionmentioning
confidence: 99%
“…1 This instruction takes into account the possibility of "nipplesconfusion" by the infant, resulting in an oral configuration and sucking pattern inappropriate for breastfeeding after exposure to the artificial nipples, 2 which contributes to early weaning. 3 Studies have shown that the use of pacifiers and/or feeding bottle favors early breastfeeding discontinuance, interferes with the development of orofacial structures, alterschild chewing and swallowing functions, 4 is associated with higher risk of cariesoccurrence 5 and teeth malocclusion, 6 besides it has been considered an important source of contamination by microorganisms harmful to health. 7 In Brazil, some regulations were established in order to supervise the trade of infant products, including pacifiers and baby bottles.…”
Section: Introductionmentioning
confidence: 99%
“…As regards to vertical discrepancy, 12 studies [3,10,14,15,18,34,36,38,39,44,45,47] investigated the relationship between breastfeeding and abnormal anterior overbite/openbite in deciduous teeth. Finally regarding sagittal discrepancy, seven studies [2,15,18,36,38,39,44]…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
“…Several studies have investigated the connection between occlusion and breastfeeding and they often came to different conclusions. Some studies [15,29] found no evidence of a connection between breastfeeding duration and malocclusion while others were able to define a precise relationship between reduced or no breastfeeding and the development of different kinds of malocclusion, i.e., skeletal class II [35], open bite [36] or posterior crossbite [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between malocclusions and pacifier use is a much-debated issue. Although no definite conclusions that are consistent with the principles of evidence-based medicine have been drawn, the general consensus regards pacifier use as harmful if it does not comply with the recommended timing and modalities [1][2][3][4] Suction is an innate reflex that appears in the prenatal stage and is one of the first muscular coordination abilities of a fetus [5]. A pacifier stimulates this reflex.…”
Section: Introductionmentioning
confidence: 99%